EFL women-learners construction of the discourse of egalitarianism and knowledge in online-talk-in-interaction - Castañeda, Adriana (Colombian Applied Linguistics Journal, 2012)
This research project sets out a ‘synthetic approach’ (Wetherell, 1998) to discourse analysis by combining elements of conversational analysis and critical discourse analysis. I explain the construction of a discourse that emerged from seven EFL women-learners online chat discussions around literature and how this discourse informs language as a socialization process. The findings suggest that while talking online, the language learning experience of these women-learners is intersected by what I labeled as the discourse of egalitarian-knowledgeable learners. It appears that through the enactment of this discourse, the students identified each other as equal status partners through conversational moves of solidarity, solicited help and repairs in miscommunication. The construction of such discourse shows that the language socialization process worked as an apprenticeship model. This project suggests that the seven EFL women learners, who participated in this research, invested in their language learning process as a result of the co-management of their power relationships as I will portray along the document by tracing the discourse and giving a polyphonic interpretation of the data.